Growth of ovarian cancer xenografts causes loss of muscle and bone mass: a new model for the study of cancer cachexia - Pin, Fabrizio; Barreto, Rafael; Kitase, Yukiko; Mitra, Sumegha; Erne, Carlie E.; Novinger, Leah J.; Zimmers, Teresa A.; Couch, Marion E.; Bonewald, Lynda F.; Bonetto, Andrea (Journal of cachexia, sarcopenia and muscle, 2018)
Background Cachexia frequently occurs in women with advanced ovarian cancer (OC), along with enhanced inflammation. Despite being responsible for one third of all cancer deaths, cachexia is generally under‐studied in OC due to a limited number of pre‐clinical animal models. We aimed to address this gap by characterizing the cachectic phenotype in a mouse model of OC. Methods Nod SCID gamma mice (n = 6–10) were injected intraperitoneally with 1 × 107 ES‐2 human OC cells to mimic disseminated abdominal disease. Muscle size and strength, as well as bone morphometry, were assessed. Tumour‐derived effects on muscle fibres were investigated in C2C12 myotube cultures. IL‐6 levels were detected in serum and ascites from tumour hosts, as well as in tumour sections. Results In about 2 weeks, ES‐2 cells developed abdominal tumours infiltrating omentum, mesentery, and adjacent organs. The ES‐2 tumours caused severe cachexia with marked loss of body weight (–12%, P < 0.01) and ascites accumulation in the peritoneal cavity (4.7 ± 1.5 mL). Skeletal muscles appeared markedly smaller in the tumour‐bearing mice (approximately –35%, P < 0.001). Muscle loss was accompanied by fibre atrophy, consistent with reduced muscle cross‐sectional area (–34%, P < 0.01) and muscle weakness (–50%, P < 0.001). Body composition assessment by dual‐energy X‐ray absorptiometry revealed decreased bone mineral density (–8%, P < 0.01) and bone mineral content (–19%, P < 0.01), also consistent with reduced trabecular bone in both femurs and vertebrae, as suggested by micro‐CT imaging of bone morphometry. In the ES‐2 mouse model, cachexia was also associated with high tumour‐derived IL‐6 levels in plasma and ascites (26.3 and 279.6 pg/mL, respectively) and with elevated phospho‐STAT3 (+274%, P < 0.001), reduced phospho‐AKT (–44%, P < 0.001) and decreased mitochondrial proteins, as well as with increased protein ubiquitination (+42%, P < 0.001) and expression of ubiquitin ligases in the skeletal muscle of tumour hosts. Similarly, ES‐2 conditioned medium directly induced fibre atrophy in C2C12 mouse myotubes (–16%, P < 0.001), consistent with elevated phospho‐STAT3 (+1.4‐fold, P < 0.001) and altered mitochondrial homoeostasis and metabolism, while inhibition of the IL‐6/STAT3 signalling by means of INCB018424 was sufficient to restore the myotubes size. Conclusions Our results suggest that the development of ES‐2 OC promotes muscle atrophy in both in vivo and in vitro conditions, accompanied by loss of bone mass, enhanced muscle protein catabolism, abnormal mitochondrial homoeostasis, and elevated IL‐6 levels. Therefore, this represents an appropriate model for the study of OC cachexia. Our model will aid in identifying molecular mediators that could be effectively targeted in order to improve muscle wasting associated with OC.